Genome analysis of a simultaneously predatory and prey-independent, novel Bdellovibrio bacteriovorus from the River Tiber, supports in silico predictions of both ancient and recent lateral gene transfer from diverse bacteria - Hobley, Laura; Lerner, Thomas R.; Williams, Laura E.; Lambert, Carey; Till, Rob; Milner, David S.; Basford, Sarah M.; Capeness, Michael J.; Fenton, Andrew K.; Atterbury, Robert J.; Harris, Maximilian A.T.S.; Sockett, R. Elizabeth (BioMed Central, 2012)
Background: